Exercise-Based Oncology Rehabilitation: LEVERAGING THE CARDIAC REHABILITATION MODEL. Issue 2 (March 2015) - Dittus, Kim L.; Lakoski, Susan G.; Savage, Patrick D.; Kokinda, Nathan; Toth, Michael; Stevens, Diane; Woods, Kimberly; O'Brien, Patricia; Ades, Philip A.
Abstract : PURPOSE: The value of exercise and rehabilitative interventions for cancer survivors is increasingly clear, and oncology rehabilitation programs could provide these important interventions. However, a pathway to create oncology rehabilitation has not been delineated. Community-based cardiac rehabilitation (CR) programs staffed by health care professionals with experience in providing rehabilitation and secondary prevention services to individuals with coronary heart disease are widely available and provide a potential model and location for oncology rehabilitation programs. Our purpose was to outline the rehabilitative needs of cancer survivors and demonstrate how oncology rehabilitation can be created using a CR model. METHODS: We identify the impairments associated with cancer and its therapy that respond to rehabilitative interventions. Components of the CR model that would benefit cancer survivors are described. An example of an oncology rehabilitation program using a CR model is presented. RESULTS: Cancer survivors have impairments associated with cancer and its therapy that improve with rehabilitation. Our experience demonstrates that effective rehabilitation services can be provided utilizing an existing CR infrastructure. Few adjustments to current CR models would be needed to provide oncology rehabilitation. Preliminary evidence suggests that cancer survivors participating in an oncology rehabilitation program experience improvements in psychological and physiologic parameters. CONCLUSIONS: Utilizing the CR model of rehabilitative services and disease management provides a much needed mechanism to bring oncology rehabilitation to larger numbers of cancer survivors. Abstract : Cancer treatment results in declines in physiologic and psychosocial parameters. Research identifies benefits for cancer survivors participating in exercise and rehabilitative interventions; however, a mechanism for providing rehabilitative services is needed. Cardiac rehabilitation provides an ideal model for developing and delivering oncology rehabilitation to cancer survivors.